Poverty among young adults in East Asia: A comparative study - Geumsun Byun; Mihee Park; Hyejin Ko (Luxembourg Income Study (LIS), 2022)
This research investigates how the poverty risk of young people changes according to their living arrangements by region, using data from the Luxembourg Income Study (LIS). Previous studies have found that the high percentage of East Asian youth living with their parents leads to low youth poverty in the region. However, the poverty rate among young East Asian adults who are married was lower than those who lived with their parents. Young people who received sufficient financial support from their parents transitioned to independence more quickly than their peers, and lowered the associated poverty risk. In other words, young people with poor parents find it difficult to become independent, so they remain living in poor households, increasing the likelihood that poverty will be transmitted across generations. Labor market instability and economic recession makes it difficult for young people with less financial help from their parents to leave their parental homes, can increase the poverty risk of young adults, especially in East Asian societies.
Keywords: 330; Armut; Junge Erwachsene; Vergleich; Ostasien; Europa